Study protocol for a randomised trial of nicotine-free cigarettes as an adjunct to usual NRT-based cessation practice, in people who wish to stop smoking - McRobbie Hayden; Glover Marewa; Grigg Michele; Bullen Chris; Howe Colin; Walker Natalie K; Laugesen Murray; Vander Hoorn Stephen; Whittaker Robyn (BMC, 2011)
Abstract Background Current smoking cessation treatments focus on addressing the pharmacological dependence of smokers on nicotine. However, new strategies are needed that address both nicotine dependence and the psychological dependence on cigarettes as the source of nicotine. Evidence from a number of small smoking cessation studies suggests that the use of cigarettes with reduced nicotine content, in combination with nicotine replacement therapy (NRT), may help reduce withdrawal symptoms and increase quit rates. This paper describes the protocol for a large randomised-controlled trial to test the effect of using nicotine-free cigarettes together with NRT on long-term quit rates. Methods/design This single-blind, randomised trial aims to recruit 1,410 participants through the national telephone-based Quitline service in New Zealand. Participants in the treatment arm will be asked to stop smoking nicotine-containing cigarettes on their chosen Quit day and smoke ad libitum nicotine-free (Quest 3) cigarettes for six weeks. At the same time people in this group will be asked to start using NRT patches, gum and/or lozenges (as recommended by Quitline) for eight weeks. Participants in the control arm will be asked to stop smoking completely on their chosen Quit day and start using NRT patches, gum and/or lozenges (as recommended by Quitline) for eight weeks. Data collection will occur at baseline, three and six weeks, and three and six months after Quit day. The primary outcome is the proportion of participants who self-report seven-day point prevalence abstinence at six months since Quit date. Discussion Smoking prevalence in New Zealand has changed little in recent years (particularly in Māori, the indigenous people of New Zealand) and additional options for smokers who want to quit are needed. Although a variety of methods are available to help, many are expensive, have side effects, and despite their use most quit attempts still fail. This trial will test the balance of benefits and risks of a new strategy for people to overcome nicotine dependence. Since smoking is the leading cause of lost healthy life years in New Zealand, if proven effective this strategy is likely to have substantial public health benefits. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12608000410358